Effects of environmental conditions on uncured prepreg characteristics and their effects on defect generation during autoclave processing. (December 2021) - Netzel, C.; Hoffmann, D.; Battley, M.; Hubert, P.; Bickerton, S.
Abstract: Primary load-bearing composite structures require high laminate quality. This is achieved by autoclave prepreg processing where high external pressures enhance consolidation. As a result, parts of simple geometry can be manufactured with void contents less than 1%. However, defects such as wrinkles and voids are typically found within more complex structures. This research investigates defect formation within autoclave prepreg processing stages and is focused on concave female corners with high laminate thickness to corner radius ratios. Experimental studies were carried out to investigate the effect of humidity exposure to uncured prepreg on defect formation during the steps of autoclave processing. It is hypothesized that moisture uptake influences uncured prepreg characteristics such as compaction behaviour, interply friction and prepreg tack, and therefore achieved quality following consolidation. Results have shown that defects already occur during the layup and debulking process and that humidity affects the uncured prepreg characteristics and thereby the consolidation quality.